Quantifying the role of federal and state taxes in mitigating income inequality - Daniel H. Cooper; Byron F. Lutz; Michael G. Palumbo (Federal Reserve Bank of Boston, 2011)
Income inequality has risen dramatically in the United States since at least 1980. This paper quantifies the role that the tax policies of the federal and state governments have played in mitigating this income inequality. The analysis, which isolates the contribution of federal taxes and state taxes separately, employs two approaches. First, cross-sectional estimates compare before-tax and after-tax inequality across the 50 states and the District of Columbia. Second, inequality estimates across time are calculated to assess the evolution of the effects of tax policies. The results from the first approach indicate that the tax code reduces income inequality substantially in all states, with most of the compression of the income distribution attributable to federal taxes. Nevertheless, there is substantial cross-state variation in the extent to which state tax policies compress the income distribution attributable to federal taxes. Cross-state differences in gasoline taxes have a surprisingly large impact on income compression, as do sales tax exemptions for food and clothing. The results of the second approach indicate that there has been little change since the early 1980s in the impact of tax policy on income inequality across almost all states.
Keywords: H22; J31; 330; Lohnstruktur; Steuerwirkung; Steuerpolitik; Ländersteuer; USA